Identification and structure elucidation of antimicrobial compounds from Lyngbya aestuarii and Aphanothece bullosa - Kumar, M.; Singh, P.; Tripathi, J.; Srivastava, A.; Tripathi, M. K.; Ravi, A. K.; Asthana, R. K. (Cellular and Molecular Biology, 2014)
Cyanobacteria are known to produce array of compounds. In an earlier report, we reported antibacterial and antifungal activities in methanolic crude extracts of laboratory grown Lyngbya aestuarii and Aphanothece bullosa isolated from Chilka Lake and local paddy field respectively. In this report the same methanolic crude extracts were subjected to TLC purification twice by altering the solvents and UV-illuminated bands bioassayed. Such UV illuminated potent bands obtained after 2nd TLC were subjected to spectroscopic analysis (UV, IR, 1H NMR and LCMS/MS). We have screened malyngolide and dragonamide C from L. aestuarii and a diterpenoid and majusculoic acid from A. bullosa. Dragonamide C and malyngolide were found to be antifungal while majusculoic acid and a diterpenoid as antibacterial. As far as our knowledge goes, this is the first ever report where fresh water A. bullosa was found to be a source of diterpenoid and majusculoic acid. Likewise, L. aestuarii was also established as a source of malyngolide and dragonamide C. This again indicated that cyanobacteria are inherently endowed with the capacity to produce metabolites according to niche and species specific manner emphasising fresh water cyanobacterial strain are as important as marine one.